Integrating multibeam sonar and underwater video data to map benthic habitats in an East Antarctic nearshore environment. (5th October 2015) - Smith, Jodie; O'Brien, Philip E.; Stark, Jonathan S.; Johnstone, Glenn J.; Riddle, Martin J.
Abstract: An integrated analysis of biological and geoscientific data collected from the nearshore marine environment of the Vestfold Hills was used to identify benthic habitats and associated communities and examine relationships between benthic community composition and environmental characteristics. A 48 km 2 area was surveyed using a multibeam echosounder system (MBES) to produce high-resolution bathymetry and backscatter intensity maps of the seabed. Epibenthic community data and in situ observations of substrate composition and seafloor bedforms and features were obtained from towed underwater video. A comparison of top-down and bottom-up approaches to defining benthic habitats was used to improve understanding of the applicability of mapping methodologies. On a broad scale, both approaches produced habitat classes distinguished largely by geomorphic features, with substrate and depth identified as the main controls of benthic community composition, however, the relationship between benthic community composition and environmental characteristics is complex with many variables contributing to differences in community composition. The top-down approach was based on geomorphic units defined using abiotic characteristics and the assemblages identified within the geomorphic were very broad with only weak distinction between assemblages. Conversely, the bottom-up approach generated additional habitat classes, identified clear defining taxa for each class, greater distinction between the benthic communities, and allowed identification of additional environmental factors (i.e. sea ice cover) that influence benthic community distribution that are not discernible from geomorphic information alone. The habitat types identified and mapped using the bottom-up approach include shallow boulder fields and exposed bedrock which are dominated by dense macroalgae communities, and steep slopes, muddy basins and sandy plains which are dominated by invertebrate communities. The results indicate that a bottom-up approach is preferable for benthic habitat mapping, however, where detailed information is not available, geomorphic information provides a reasonable indication of the distribution of benthic habitats and communities. This study highlights the utility of multibeam sonar for interpretation of seafloor morphology and substrate and the multibeam data provide a physical framework for understanding benthic habitats and the distribution of benthic communities. This research provides the scientific context and spatial framework for managing the Vestfold Hills nearshore marine environment and provides a baseline for assessing environmental change. Graphical abstract: Highlights: Collected high-resolution multibeam sonar and underwater video in Antarctic waters. Compared top-down and bottom-up approaches to identifying benthic habitats. Geomorphic units are useful for characterising benthic communities on broad scales. Six discrete benthic biotopes were defined and mapped. Bottom-up approach needed to fully capture biotic–abiotic relationships.